Giant Hydatid Cyst: in the Interventricular Septum of a Pregnant Woman - Tetik, Omer (2002)
A 25-year-old woman, pregnant for 38 weeks, was admitted to our clinic with dyspnea. Transthoracic echocardiography revealed a large cyst that originated from the left side of the interventricular septum, decreasing left ventricular volume and almost entirely obstructing the left ventricular outflow tract. Cardiac magnetic resonance imaging confirmed a grade 1 hydatid cyst, which measured 61 × 59 × 66 mm. The cyst was excised after cesarean section. Extirpation required the creation of a small septal defect, which we closed without a patch, by suturing the septum directly to the left ventricular wall. The patient was discharged without symptoms. The case reported here is of particular interest not only because a hydatid cyst is rarely seen in the interventricular septum, but because a giant hydatid cyst obstructing the left ventricular outflow tract is very rare in pregnancy. (Tex Heart Inst J 2002;29:333–5)